Biodegradable copolyesters based on a "soft" isohexide building block with tunable viscoelasticity and self-adhesiveness. Issue 31 (20th July 2022) - Lin, Yiming; Ye, Mengting; Zhang, Xu; Chen, Yong; Chen, Ye; Wu, Jing; Wang, Huaping
Abstract : PBIA copolyesters synthesised using a novel glycosylated monomer (IIDMC) have faster degradation and tunable self-adhesiveness. Abstract : With the aim of developing novel biodegradable functional polymers, a series of copolyesters (PBIA) with low T g values and tunable self-adhesiveness were synthesized by utilizing a unique "soft" isohexide building block, i.e. isoidide-2, 5-dimethyl carboxylate (IIDMC). PBIA copolyesters were obtained via a cascade polycondensation protocol with M n values of 11 000–25 100 g mol −1 and effective suppression of gelation. The copolyesters with low (<60 mol%) and high (>60 mol%) contents of IIDMC are semi-crystalline, while those with medium amounts (30–60 mol%) of IIDMC are amorphous, highly sticky materials. Depending on the chemical compositions, the T g values of the copolyesters can be tuned from −50 to 1 °C. The sticky PBIA copolyesters are suitable for application as precursors of pressure sensitive adhesives by exhibiting shear moduli < 10 5 Pa to ensure sufficient contact and wetting with the substrate. The presence of IIDMC units effectively induces fast degradation of the copolymers, and the hydrolytic and enzymatic degradation performances are even superior to those of the PBA polyester. The results demonstrate the potential of IIDMC, a unique "soft" isohexide building block, to construct novel functional polymers, e.g. adhesives with good biodegradability.